2014
DOI: 10.1016/j.jbankfin.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and predicting the CBOE market volatility index

Abstract: This paper performs a thorough statistical examination of the time-series properties of the daily market volatility index (VIX) from the Chicago Board Options Exchange (CBOE). The motivation lies not only on the widespread consensus that the VIX is a barometer of the overall market sentiment as to what concerns investors' risk appetite, but also on the fact that there are many trading strategies that rely on the VIX index for hedging and speculative purposes. Preliminary analysis suggests that the VIX index di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
113
3
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(132 citation statements)
references
References 47 publications
7
113
3
9
Order By: Relevance
“…However, unlike the findings of Fernandes et al (2014) for the US market, we find that incorporating domestic macroeconomic variables into the HAR model framework improves both insample fitting and out-of-sample forecasting performance. More importantly, we find that the S&P 500 spot returns and VIX of the US market play a dominant role in explaining the VKOSPI dynamics and predicting its future volatility.…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, unlike the findings of Fernandes et al (2014) for the US market, we find that incorporating domestic macroeconomic variables into the HAR model framework improves both insample fitting and out-of-sample forecasting performance. More importantly, we find that the S&P 500 spot returns and VIX of the US market play a dominant role in explaining the VKOSPI dynamics and predicting its future volatility.…”
Section: Introductioncontrasting
confidence: 99%
“…Given the above considerations, our study is inspired by two recent influential studies: Corsi (2009) and Fernandes et al (2014). Corsi (2009) suggests a new way to analyze volatilities based on their persistence and long memory properties, while Fernandes et al (2014) examine the time-series properties of the VIX using new advances in econometrics and report that the pure heterogeneous autoregressive (HAR) model outperforms the extended HAR models, which incorporate exogenous macro-finance variables in forecasting, particularly shortterm ahead forecasting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, these differences could be attributed to the specific characteristics and behaviour of the Korean options market. Fernandes et al (2014) also showed that the relationship between daily changes in the VIX volatility index and contemporary performance of the market index S & P 500 is strongly negative during the period from 2 January 1992 to 15 January 2013. However, controlling asymmetric effects, they stated that there is no significant influence of the S & P 500 variations on the evolution of the VIX index for all time horizons considered in their study.…”
Section: Literature Reviewmentioning
confidence: 93%